Estimating the Threat Effect of Active Labour Market Programmes - Michael Rosholm; Michael Svarer (Institute for the Study of Labor (IZA), 2004)
We combine two techniques to consistently estimate the effect of active labour market programmes and, in particular, active labour market policy regimes. Our aim is to explicitly estimate the threat effect of active labour market programmes. Based on Danish data (1998- 2002) from administrative registers we find a strong and significantly positive threat effect. The threat effect is shown to reduce average unemployment duration by approximately three weeks. The implications of this result are discussed.
Keywords: C41; J64; 330; active labour market policy; threat effect; timing-of-events; duration model; Arbeitsmarktpolitik; Beschäftigungseffekt; Dänemark